Encouraging the Quality of Higher Education in Indonesia: The Importance of Doctoral Education for Lecturers - Dhanar Intan Surya Saputra; Widya Tri Purnomo; Raflyan Akhyar Ramadhan; Ikhwan Fahrialselofianto; Dinar Mustofa (Peneliti Teknologi Teknik Indonesia, 2023)
Higher education plays a crucial role in advancing Indonesia's progress. As key providers of quality education, lecturers are vital in shaping competent graduates and competitive educational institutions. Enhancing lecturers' professionalism and higher education quality is achieved through postgraduate doctoral education. This article delves into the significant role of doctoral studies for lecturers in Indonesia and its impact on improving higher education quality.¬ Analyzing reliable secondary data, it highlights the increasing participation of lecturers in doctoral education. Doctoral graduates demonstrate enhanced academic competence, research skills, and contributions to science and technology. Their profound knowledge enables them to deliver more pertinent, current, and evidence-based teaching, while also fueling innovation and research. Nonetheless, challenges persist, such as budget constraints and limited suitable study programs and funding. Consequently, strategic efforts, including increased financial support, relevant program development, and international collaborations, are essential in ensuring the success of Doctoral education for lecturers. Implementing these measures can boost lecturer participation, thereby positively influencing higher education quality and fostering a highly skilled workforce in Indonesia.